2007
DOI: 10.1063/1.2748079
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of 1040nm semiconductor disk lasers on a nanosecond time scale

Abstract: The nanosecond dynamics of near-infrared semiconductor disk lasers is investigated experimentally and theoretically. Lasing and photoluminescence following barrier pumping are analyzed. Their spectral and temporal features such as luminescence overshoot and clamping, delay of lasing onset, and redshift of the emission are explained by a rate equation model taking into account the microscopic gain and luminescence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…These measurements can then be compared to rate equation simulations based on parameters stemming from microscopic simulations, as demonstrated e.g. for 1, 040 nm disk lasers (Diehl et al 2007). …”
Section: Relaxation Oscillations Delay and Decaymentioning
confidence: 99%
“…These measurements can then be compared to rate equation simulations based on parameters stemming from microscopic simulations, as demonstrated e.g. for 1, 040 nm disk lasers (Diehl et al 2007). …”
Section: Relaxation Oscillations Delay and Decaymentioning
confidence: 99%
“…For the latter we use the experimentally estab- lished value of 0.1 nm/K. 12,21,24 This resonator shift introduces an additional temperature dependence on the modal gain on top of the thermal modifications of the material gain. The presence of an AR coating reduces this effect because the subcavity resonance is less pronounced.…”
Section: Steady-state Characteristicsmentioning
confidence: 99%
“…This is common practice in electrically-driven semiconductor devices and has been used in particular for devices used for micro-displaytype projection/display applications [103,104]. Recent pulsed pumping experiments [105,106] have shown that this method improves the maximum output power achievable with a given SDL chip as long as the pulse duration is shorter than a few hundred nanoseconds, the typical transient time associated with SDL heating. It was also demonstrated that the use of a heatspreader has negligible impact on laser performance for these considered timescales [105].…”
Section: Power Scalingmentioning
confidence: 99%